Frog Adventure: 2D Based Platformer Game Design with HTML5 - Tawakal, Rayendra; Hezma, Mela; Cahyani, Dewi Regita (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
A game is an activity or form of entertainment that involves players in a structured system of rules. Typically, games involve clear goals, challenges, interaction, and decision making by players. Games can be played individually or in groups, either physically or via electronic media such as computers, game consoles, or mobile devices. This report provides in-depth information about the game